Simple Additive Weighting Method for Internet Service Provider Vendor Selection Decision Support System - Muhammad Rafli; Winny Purbaratri; Agnes Novita Ida Safitri; Budi Indiarto; Fandan Dwi Nugroho Wicaksono (bit-Tech, 2025)
The increasing demand for high-speed, stable, and reliable internet services at IKPIA Perbanas—driven by educational, research, and administrative needs—has posed challenges in selecting the most suitable Internet Service Provider (ISP). With numerous vendors offering diverse bandwidth packages and pricing, a structured and objective decision-making method is essential. This study proposes the development of a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to assist in the selection of the most appropriate ISP. The research adopts a quantitative approach, utilizing both primary and secondary data. Primary data were collected through a questionnaire distributed via Google Forms to five experts comprising the tender selection team. Secondary data were obtained through observation and interviews. Seven key criteria were identified: bandwidth, benefit, experience, service level agreement (SLA), support, hardware, and security. Each criterion was weighted and evaluated using the SAW method. The resulting system calculated normalized performance ratings and preference values for each vendor. The analysis showed that PT. B achieved the highest preference value (0.97), followed by PT. E (0.93), indicating PT. B as the most suitable vendor. The developed system successfully supports transparent, criteria-based ISP selection, enhancing the efficiency and objectivity of the procurement process at IKPIA Perbanas.